A Transdiploic Cerebrospinal Fluid Diversion Device: Potential Use in Intracranial Hypertension Associated with Traumatic Brain Injury - Moscote-Salazar, Luis Rafael; Agrawal, Amit; Florez-Perdomo, William A.; Chacon, Ariana (Indian Journal of Neurotrauma, 2024)
Intracranial hypertension (IH) is a critical condition in neurocritical care and needs effective management to avoid severe outcomes like brain herniation and cerebral ischemia. External ventricular drains, although effective in reducing intracranial pressure, pose risks of infection, hemorrhage, and malfunction. This technical note present the transdiploic cerebrospinal fluid (CSF) diversion device, an alternative technique for CSF diversion utilizing the parietal diploic venous system.
Keywords: cerebrospinal fluid diversion; neurotrauma; ventriculostomy; diploic venous system; intracranial hypertension